Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $f(z)$ be analytic in the disk $|z|<R \ \ \ (R>1)$ except for a simple pole at a point $z_0$, $|z_0|=1$. Consider the expansion $f(z)=a_0+a_1 z+ \cdots$, and show that $$\lim_{n \to \infty} \frac {a_n} {a_{n+1}}=z_0$$

All my attempts failed. I wanted to use the Laurent series at $z_0$ but the problem needs expansion at $0$.

share|cite|improve this question
up vote 6 down vote accepted

There is an $a\ne0$ such that the principal part of $f$ at $z_0$ is given by $z\mapsto{a\over z-z_0}$. The function $g(z):=f(z)-{a\over z-z_0}$ has a removable singularity at $z_0$ and is analytic otherwise in $D_R$, which implies that $g$ is in fact analytic in $D_R$. So $g$ has a Taylor expansion $g(z)=\sum_{n=0}^\infty b_nz^n$ which is convergent for $|z|<R$, in particular at $z:={1\over2}(1+R)$. Therefore one necessarily has $$|b_n|\leq\Bigl({2\over1+R}\Bigr)^n\qquad(n>n_0)\ ;$$ which implies $\lim_{n\to\infty} b_n=0$. On the other hand, $${a\over z-z_0}=-{a/z_0 \over 1-(z/z_0)}=-{a\over z_0}\sum_{n=0}^\infty\Bigl({z\over z_0}\Bigr)^n\ .$$ Now $f(z)={a\over z-z_0}+g(z)$. Therefore the Taylor coefficients $a_n$ of $f$ are given by $$a_n=-{a\over z_0^{n+1}} + b_n\ ,$$ from which we get $${a_n\over a_{n+1}}={-a/z_0^{n+1} +b_n\over -a/z_0^{n+2}+b_{n+1}}=z_0{a-b_n z_0^{n+1} \over a - b_{n+1}z_0^{n+2}}\to z_0\qquad(n\to\infty)\ .$$

share|cite|improve this answer
Thanks, I understood all the things but one: In first sentence, how can you notice instantly the existence of $a$ and $g(z)$? My understanding lacks something: Since $f(z)$ has a pole at $z_0$, it can be expressed as Laurent series at $z_0$, so $f(z)= a/(z-z_0) + g(z)$ where $g(z)$ is analytic inside the disk of radius $R-1$ at $z_0$. So the analytic radius of $g(z)$ is different for yours. – Gobi Sep 17 '12 at 13:14
@Gobi: I have explained it in my edit. – Christian Blatter Sep 17 '12 at 13:46

Consider $\displaystyle f(z) = \frac{g(z)}{z-z_0}$. Since $f$ has a simple pole at $z_0$, $g$ is holomorphic on the disc.

Now, let $f = \sum a_nz^n, g=\sum b_nz^n$. Then, $\sum b_nz^n = (z-z_0)\sum a_nz^n$. Comparing the coefficients, you get $b_{n+1} = a_n - z_0a_{n+1}$.

As $n \to \infty$, $b_n \to 0$ while $a_n$ will not tend to $0$.

share|cite|improve this answer
I appreciate your answer, but how can I get the last statement? – Gobi Sep 15 '12 at 1:16
Well, $b_n \to 0$ as a result of the radius of convergence being $>1$. However, we need something a bit stronger than $a_n \not\to 0$ to conclude the claim. For instance if $a_n=0$ infinitely often the limit is not even well-defined. I think to make this argument work we need to $a_n$ bound away from $0$ for all large $n$. – Erick Wong Sep 15 '12 at 3:30

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.